Pengembangan Pengembangan Variasi Latihan Daya Tahan Berbasis Permainan dengan Uji Coopeer test pada Mahasiswa PJKR C Stambuk 2023: Pengembangan Variasi Latihan Daya Tahan Berbasis Permainan dengan Uji Coopeer test pada Mahasiswa PJKR C Stambuk 2023 - Ade Ros Riza; Fauziah Amanda Rambe; Muhammad Reza Nasution; Remika Maretama Situmorang; Sundari Ramahsita; Ingat Berkat Giawa; Winsara Diwa (SPORTIVE: Journal Of Physical Education, Sport and Recreation, 2026)
The low variation of weight training in physical education learning impacts on the improvement of aerobic fitness and suboptimal student motivation. This study aims to develop and test the effectiveness of a structured and adaptive game-based weight training model in increasing VO₂max and student participation. The method used is Research and Development (R&D) with the stages of needs analysis, model design, limited trials, and evaluation. The research subjects were 20 students. The research instruments included a 12-minute Cooper test, observation sheets, and expert validation questionnaires. Data analysis used a paired sample t-test at a significance level of 0.05. The results showed a significant increase in VO₂max from an average of 35.2 ± 2.8 to 39.6 ± 3.1 (Δ = 4.4), with a t(19) value = 8.72; p = 0.000 (p < 0.05). The distance covered increased from 2,400 ± 210 meters to 2,780 ± 230 meters, and student participation increased by 27%. The uniqueness of this study lies in the integration of game, competition, and cooperation elements in one systematic training model. The conclusion shows that the game-based endurance training model is significantly effective in increasing aerobic capacity, motivation, and student engagement, and has the potential to be an innovative alternative in physical education learning in higher education that is more active, adaptive, and oriented towards improving the quality of learning outcomes holistically.